Dectin-1 Positive Dendritic Cells Expand after Infection with Leishmania major Parasites and Represent Promising Targets for Vaccine Development - Zimara, Nicole; Chanyalew, Menberework; Aseffa, Abraham; van Zandbergen, Ger; Lepenies, Bernd; Schmid, Maximilian; Weiss, Richard; Rascle, Anne; Wege, Anja Kathrin; Jantsch, Jonathan; Schatz, Valentin; Brown, Gordon D.; et al. (Frontiers in Immunology, 2018)
Resistant mouse strains mount a protective T cell mediated immune response upon infection with Leishmania (L.) parasites. Healing correlates with a T helper (Th) cell type 1 response, characterized by a pronounced IFN-γ production while susceptibility is associated with an IL-4 dependent Th2-type response. It has been shown that dermal dendritic cells (DC) are crucial for inducing protective Th1-mediated immunity. Additionally, there is growing evidence that C-type lectin receptor (CLR)-mediated signaling is involved in directing adaptive immunity against pathogens. However, little is known about the function of the CLR Dectin-1 in modulating Th1- or Th2-type immune responses by DC subsets in leishmaniasis. We characterized the expression of Dectin-1 on CD11c+ DCs in peripheral blood, at the site of infection, and skin-draining lymph nodes (SDLN) of L. major infected C57BL/6 and BALB/c mice and in peripheral blood of patients suffering from cutaneous leishmaniasis (CL). Both mouse strains responded with an expansion of Dectin-1+ DCs within the analyzed tissues. In accordance with the experimental model, Dectin-1+ DCs expanded as well in the peripheral blood of CL patients. To study the role of Dectin-1+ DCs in adaptive immunity against L. major, we analyzed the T cell stimulating potential of bone marrow-derived dendritic cells (BMDCs) in the presence of the Dectin-1 agonist Curdlan. These experiments revealed that Curdlan increases the maturation of BMDCs and the expansion of Leishmania-specific CD4+ T cells. Based on these findings, we evaluated the impact of Curdlan/Dectin-1 interactions in experimental leishmaniasis and were able to demonstrate that the presence of Curdlan at the site of infection modulates the course of disease in BALB/c mice: Wildtype BALB/c mice treated intradermally with Curdlan developed a protective immune response against L. major whereas Dectin-1-/- BALB/c mice still developed the fatal course of disease after Curdlan treatment. Furthermore, the vaccination of BALB/c mice with a combination of soluble Leishmania antigens and Curdlan was able to provide a partial protection from severe leishmaniasis. These findings indicate that the ligation of Dectin-1 on DCs acts as an important checkpoint in adaptive immunity against L. major and should therefore be considered in future whole- organism vaccination strategies.